Metamorphic Testing in Bioinformatics Software: A Case Study on Metagenomic Assembly - Stacy, Brook; Hauzel, Jason; Lindvall, Mikael; Porter, Adam; Pop, Mihai (Proceedings of the 7th International Workshop on Metamorphic Testing, 2022)
MetaCompass is a metage nomic assembly tool developed by the Pop Lab at the University of Maryland, College Park [2]. Such tools are vital for studying the DNA of the variety of microorganisms present in mixed environmental samples, but they can be difficult to test due to the infeasibility of assessing the correctness of the output of a given test case. In this paper, we demonstrate a simple metamorphic test that detects inconsistencies in the popular assem-bly tools MEGAHIT [7] and Pilon [11], upon which MetaCompass relies. These inconsistencies were not detected during the development process by standard testing procedures, despite the fact that they may be introducing undesirable noise into MetaCompass's results. Our results suggest that metamorphic testing is a valuable tool for finding otherwise subtle defects in metagenomic assembly software.